Non-Financial Performance and Cognitive Factors on The Performance - R Rapina; R Ridwan; Yenni Carolina (Jurnal ASET (Akuntansi Riset), 2023)
Improved customer service can improve a bank's reputation. Bank reputation is not only determined by financial health but also by non-financial performance factors. This research measures how non-financial performance influences bank performance. The approach used is quantitative, with primary data acquired through the distribution of questionnaires to research participants and augmented by interview processes. The data is analyzed using Partial Least Squares. This study states that there is an effect of non-financial performance on banking performance. Organizations use Nonfinancial Performance Measures (NPM) measurement as an approach to establish goals and relate them to the vision and strategy of the organization. The variables that mediate the relationship between non-financial performance and banking performance are interpersonal trust and psychological empowerment which are found to have a significant direct effect on banking performance. The implications of this research are aimed at the banking industry to be able to maintain its performance by paying attention to factors of non-financial size. The implementation of non-financial performance measurement enables banks to gain a more comprehensive understanding of the factors contributing to the long-term success of the company. Additionally, this measurement assists banks in taking necessary actions to achieve their goals and maintain a competitive position in the market. The difference between this study and other studies is that it measures banking performance from the non-financial side by mediating cognitive mechanisms, namely psychological empowerment and interpersonal trust in banking performance in Indonesia.